The Implementation of English Creative Writing Learning Based on Al Quran and Hadith - Prasetya, Eska Perdana; Salati Asmahasanah; Tohir Solehudin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2024)
This comprehensive study aims to investigate the English creative writing learning process at SMP LabSchool Kebayoran Baru. Employing the learning ethnography method, the research focuses on detailing the planning, implementation, and evaluation of creative writing education in English, as well as gauging students' appreciation for various approaches and models. The study reveals the integration of creative writing elements such as short stories, song lyrics, and biographies into the curriculum. Teachers employ diverse methods like the question-and-answer technique, discovery learning, and Project Based Learning (PBL). Poetry, short stories, and song lyrics developed by teachers constitute significant components of the creative writing classes. The roles of teachers encompass acting as informants, organizers, and motivators, while students are expected to listen attentively, adhere to school rules, and actively engage in classroom learning. Technological tools like language laboratories, e-learning applications, and supporting platforms such as wordwalls, quizizz, and kahoot, with the language lab as a central infrastructure, are utilized. Evaluation criteria include content, organization, vocabulary, language use, and creativity. Additionally, the study identifies a strong correlation between LabSchool's core values and the school culture, where the Merdeka Curriculum facilitates independent learning by providing ample time for concept deepening and competency strengthening.